Influência Do Capital Social No Transtorno Mental Comum - Régio, Ana Paula Santos Castro (2024)
Common Mental Disorders (CMD), mainly the two main diagnostic classes, depression and anxiety, and they have a high prevalence in the world population, according to the WHO 1 billion people living with some type of mental disorder in 2019. We observed the influence that social and family relationships and participation in groups can bring to an individual’s life. Social Capital is defined by friendship relationships, support networks, coexistence groups that can exert a positive or negative influence on the individual's life. Objective: To analyze the influence of social capital on common mental disorders in the Adventist population in the city of Greater São Paulo, participants in the Advent study. Methodology: prospective observational study, developed at the ELSA Clinical Research Center of the University Hospital of the Faculty of Medicine of the University of São Paulo, with 1404 participants of both sexes, who declare themselves as active members of the Seventh-day Adventist Church in the State of São Paulo Paulo, between March 2013 and August 2016, aged between 35 and 74 years old. Results: CMD was more common in women, individuals who had low levels of prestige, education and social support were more likely to have CMD. Those who had an income of less than 1.8 minimum wages were more likely to have CMD, as were those who had a level of education greater than or equal to 8 years and those who reported having more than 7 residents in the house. Conclusion: social capital influenced the development of mental disorders in the studied population.